Earnings Performance Targets in Annual Incentive Plans and Management Earnings Guidance - Martin, Xiumin; Seo, Hojun; Yang, Jun; Kim, Daniel Sungyeon; Martel, Jordan (The Accounting Review, 2023)
ABSTRACT We study how corporate boards set earnings performance targets in CEOs’ annual incentive plans (AIPs) and the implications for strategic management earning guidance. We find that corporate boards rely on management and analyst information in setting the earnings performance targets, and the weight placed on each signal increases with its precision. We also find that management earnings guidance issued before compensation committee meetings (“event-window management forecast (MF)”) is more pessimistic than that issued by the same firm at other times. The pessimism in the event-window MF is more pronounced when the expected managerial benefits of having lower performance targets are greater. Ex post, the event-window MF pessimism is associated with higher bonus payouts to CEOs. We use a theoretical framework to illustrate how the use of earnings performance targets might drive our findings. This study highlights boards’ tradeoffs in designing executive compensation and the resulting managerial strategic disclosure. JEL Classifications: G34; M41; M52.